Epidemiologic features of overseas imported malaria in the People's Republic of China. (December 2016) - Li, Zhongjie; Zhang, Qian; Zheng, Canjun; Zhou, Sheng; Sun, Junling; Zhang, Zike; Geng, Qibin; Zhang, Honglong; Wang, Liping; Lai, Shengjie; Hu, Wenbiao; Clements, Archie; et al.
Abstract Background With the dramatic increase in international travel among Chinese people, the risk of malaria importation from malaria-endemic regions threatens the achievement of the malaria elimination goal of China. Methods Epidemiological investigations of all imported malaria cases were conducted in nine provinces of China from 1 Nov, 2013 to 30 Oct, 2014.Plasmodium species, spatiotemporal distribution, clinical severity, preventive measures and infection history of the imported malaria cases were analysed using descriptive statistics. Results A total of 1420 imported malaria cases were recorded during the study period, withP. falciparum (723 cases, 50.9 %) andP. vivax (629 cases, 44.3 %) being the two predominant species. Among them, 81.8 % of cases were in Chinese overseas labourers. The imported cases returned from 41 countries, mainly located in Africa (58.9 %) and Southeast Asia (39.4 %). About a quarter (25.5 %, 279/1094) of counties in the nine study provinces were affected by imported malaria cases. There were 112 cases (7.9 %) developing complicated malaria, including 12 deaths (case fatality rate: 0.8 %). Only 27.8 % of the imported cases had taken prophylactic anti-malarial drugs. While staying abroad, 27.7 % of the cases had experienced two or more episodes of malaria infection. The awareness of clinical manifestations and the capacity for malaria diagnosis were weak in private clinics and primary healthcare facilities. Conclusions Imported malaria infections among Chinese labourers, returned from various countries, poses an increasing challenge to the malaria elimination programme in China. The risk of potential re-introduction of malaria into inland malaria-free areas of China should be urgently addressed.